2014
DOI: 10.1063/1.4868640
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical spectroscopic characterization at low temperatures of detectable sulfur-organic compounds: Ethyl mercaptan and dimethyl sulfide

Abstract: Microwave and ab initio studies of rare gas-methane van der Waals complexes J. Chem. Phys. 120, 9047 (2004); 10.1063/1.1691743 This article is copyrighted as indicated in the article. Reuse of AIP content is subject to the terms at: http://scitation.aip.org/termsconditions. Highly correlated ab initio methods are used for the spectroscopic characterization of ethyl mercaptan (CH 3 CH 2 32 SH, ETSH) and dimethyl sulfide (CH 3 32 SCH 3 , DMS), considering them on the vibrational ground and excited torsional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 71 publications
1
49
0
Order By: Relevance
“…The values of these interaction terms are comparable to those found for methyl acetate (34 cm −1 for V 12S and −3.5 cm −1 for V 12C ; Tudorie et al 2011). For DMS, the effective two-dimensional PES derived by Senent et al (2014) at the CCSD(T)-F12/VTZ-F12 level shows only a very small dependence of the torsional modes on the other small amplitude vibrations, after the authors verified the validity of such a 2D Hamiltonian with a full dimensional anharmonic analysis. The effective PES is given by V eff (α 1 , α 2 ) = 712.532 − 354.641 (cos 3α 1 + cos 3α 2 ) + 0.583 cos 3α 1 cos 3α 2 −2.767 (cos 6α 1 +cos 6α 2 ) + 0.719 (cos 3α 1 cos 6α 2 + cos 6α 1 cos 3α 2 ) + 0.263 cos 6α 1 cos 6α 2 + 6.075 sin 3α 1 sin 3α 2 which can be partly compared to the results in our fit V eff (α 1 , α 2 ) = 735.784 − 367.892(cos 3α 1 + cos 3α 2 ) (4) − 32.86 sin 3α 1 sin 3α 2 .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The values of these interaction terms are comparable to those found for methyl acetate (34 cm −1 for V 12S and −3.5 cm −1 for V 12C ; Tudorie et al 2011). For DMS, the effective two-dimensional PES derived by Senent et al (2014) at the CCSD(T)-F12/VTZ-F12 level shows only a very small dependence of the torsional modes on the other small amplitude vibrations, after the authors verified the validity of such a 2D Hamiltonian with a full dimensional anharmonic analysis. The effective PES is given by V eff (α 1 , α 2 ) = 712.532 − 354.641 (cos 3α 1 + cos 3α 2 ) + 0.583 cos 3α 1 cos 3α 2 −2.767 (cos 6α 1 +cos 6α 2 ) + 0.719 (cos 3α 1 cos 6α 2 + cos 6α 1 cos 3α 2 ) + 0.263 cos 6α 1 cos 6α 2 + 6.075 sin 3α 1 sin 3α 2 which can be partly compared to the results in our fit V eff (α 1 , α 2 ) = 735.784 − 367.892(cos 3α 1 + cos 3α 2 ) (4) − 32.86 sin 3α 1 sin 3α 2 .…”
Section: Discussionsupporting
confidence: 62%
“…As stated in Senent et al (2014), the long distance between the two methyl groups in DMS makes the coupling effects associated with this top-top torsional mode near the equilibrium configuration rather small in comparison with its oxygen analog dimethyl ether. As shown in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is quite evident that these sulphur compounds are of prime importance in understanding the interactions occurring in the atmospheric environments. Among many sulphur-organic compounds, DMS conformers have been detected in low temperature regions of interstellar medium [4]. The second molecule of the DMS series, diethyl sulphide (DES), is used in plating baths for gold and silver and as a solvent for anhydrous minerals [5].…”
Section: Introductionmentioning
confidence: 99%
“…28 However, based on the Gibbs free energy difference of 1.92 kJ mol −1 between trans and gauche forms, the relative abundances of trans and gauche forms were estimated to be 19% and 81%, respectively. 29 However, conformerspecific ionization spectroscopy studies on ethanethiol revealed only gauche conformer of ethanethiol to be present in a molecular jet.…”
Section: B Ethanethiolmentioning
confidence: 99%